LINGUISTIC CHALLENGES IN THE ERA OF DIGITAL TECHNOLOGY DEVELOPMENT - Abdurahmonova, Husnorakhon (Effective scientific journals, 2026)
The rapid development of digital technologies has significantly transformed communication practices, language structures, and linguistic research methodologies. This article examines the major linguistic challenges emerging in the era of digitalization, including language change in online discourse, artificial intelligence and natural language processing, multilingualism in digital spaces, digital literacy, and the preservation of minority languages. Drawing upon sociolinguistics, computational linguistics, and discourse analysis, the study explores how digital platforms reshape language norms, grammar, semantics, and pragmatic conventions. The research also analyzes the implications of algorithmic mediation, machine translation, and large language models for linguistic theory and language policy. The findings suggest that digital technologies simultaneously accelerate linguistic innovation and create structural risks such as linguistic homogenization, data bias, and erosion of linguistic diversity. The article argues for an interdisciplinary approach to address emerging linguistic challenges in the digital era.